Modified pea apyrase has altered nuclear functions and enhances the growth of yeast and Arabidopsis - Tripathy, Manas K.; Wang, Huan; Slocum, Robert D.; Jiang, Han-Wei; Nam, Ji-Chul; Sabharwal, Tanya; Veerappa, Roopadarshini; Brown, Katherine A.; Cai, Xingbo; Faull, Peter Allen; Clark, Greg; Roux, Stanley J. (Frontiers in Plant Science, 2025)
Apyrases (NTPDases) regulate growth and development in multiple eukaryotic organisms and function in multiple sub-cellular locales. An earlier report showed that the ectopic expression of psNTP9 (PS), a chromatin-associated pea (Pisum sativum) apyrase, enhanced the uptake of inorganic phosphate (Pi) and increased the growth of yeast and Arabidopsis. In this follow-up study, we generated a modified form of PS, abbreviated DM (“double mutant”), in which two-point mutations, S208L and P216R, were introduced into its DNA-binding domain. Ectopic expression of DM increased the growth of yeast and Arabidopsis, the seed yield of Arabidopsis, and the Pi content of yeast and Arabidopsis grown in Murashige-Skoog media beyond that effected by PS. Both the PS and DM proteins co-purified with nuclei and chromatin-associated proteins from yeast and Arabidopsis, and expression of their transgenes in these model organisms produced gene expression profiles that would be expected to promote increased growth and Pi uptake. Chromatin immunoprecipitation (ChIP)-seq analyses showed that PS and DM have largely different binding sites on yeast chromatin, including sites in promoters of numerous genes that are differentially-expressed in PS and DM transgenic lines. These results are consistent with the hypothesis that the effects of ectopically expressing the pea apyrase in yeast and in Arabidopsis are mediated, at least in part, by its activities in the nucleus that impact transcription.